Glucose regulates tissue-specific chondro-osteogenic differentiation of human cartilage endplate stem cells via O-GlcNAcylation of Sox9 and Runx2 - Chao Sun; Weiren Lan; Bin Li; Rui Zuo; Hui Xing; Minghan Liu; Jie Li; Yuan Yao; Junlong Wu; Yu Tang; Huan Liu; Yue Zhou (Stem Cell Research & Therapy, 2019)
Abstract Background The degenerative disc disease (DDD) is a major cause of low back pain. The physiological low-glucose microenvironment of the cartilage endplate (CEP) is disrupted in DDD. Glucose influences protein O-GlcNAcylation via the hexosamine biosynthetic pathway (HBP), which is the key to stem cell fate. Thiamet-G is an inhibitor of O-GlcNAcase for accumulating O-GlcNAcylated proteins while 6-diazo-5-oxo-l-norleucine (DON) inhibits HBP. Mechanisms of DDD are incompletely understood but include CEP degeneration and calcification. We aimed to identify the molecular mechanisms of glucose in CEP calcification in DDD. Methods We assessed normal and degenerated CEP tissues from patients, and the effects of chondrogenesis and osteogenesis of the CEP were determined by western blot and immunohistochemical staining. Cartilage endplate stem cells (CESCs) were induced with low-, normal-, and high-glucose medium for 21 days, and chondrogenic and osteogenic differentiations were measured by Q-PCR, western blot, and immunohistochemical staining. CESCs were induced with low-glucose and high-glucose medium with or without Thiamet-G or DON for 21 days, and chondrogenic and osteogenic differentiations were measured by Q-PCR, western blot, and immunohistochemical staining. Sox9 and Runx2 O-GlcNAcylation were measured by immunofluorescence. The effects of O-GlcNAcylation on the downstream genes of Sox9 and Runx2 were determined by Q-PCR and western blot. Results Degenerated CEPs from DDD patients lost chondrogenesis, acquired osteogenesis, and had higher protein O-GlcNAcylation level compared to normal CEPs from LVF patients. CESC chondrogenic differentiation gradually decreased while osteogenic differentiation gradually increased from low- to high-glucose differentiation medium. Furthermore, Thiamet-G promoted CESC osteogenic differentiation and inhibited chondrogenic differentiation in low-glucose differentiation medium; however, DON acted opposite role in high-glucose differentiation medium. Interestingly, we found that Sox9 and Runx2 were O-GlcNAcylated in differentiated CESCs. Finally, O-GlcNAcylation of Sox9 and Runx2 decreased chondrogenesis and increased osteogenesis in CESCs. Conclusions Our findings demonstrate the effect of glucose concentration on regulating the chondrogenic and osteogenic differentiation potential of CESCs and provide insight into the mechanism of how glucose concentration regulates Sox9 and Runx2 O-GlcNAcylation to affect the differentiation of CESCs, which may represent a target for CEP degeneration therapy.